An Analysis of Forensic Accounting and Internal Controls Through Accounting Information Systems in Mitigating Financial Report Manipulation - Murdifin Azhar (Majapahit Journal of Islamic Finance and Management, 2025)
According to the report from the Association of Certified Fraud Examiners (ACFE) (2022), fraud occurred globally between January 2020 and September 2021, with a total of 2,110 reported cases resulting in losses exceeding $3.6 billion—approximately $1,783,000 per case—and involving 133 countries. The role of forensic accounting and internal control based on Accounting Information Systems (AIS) is essential in preventing financial statement manipulation. This study employs a qualitative research method with a descriptive approach to analyze the role of AIS-based internal control and forensic accounting in detecting financial statement manipulation. The results of the study indicate that forensic accounting plays a significant role in uncovering financial statement fraud. Through comprehensive analysis, forensic accounting successfully deconstructed the complex structure of Special Purpose Entities (SPEs) and identified suspicious transaction patterns, including the transfer of debt and losses to other entities. Furthermore, the findings also reveal that by integrating internal control with AIS, companies are able not only to detect irregularities in financial data but also to trace audit trails and prevent unauthorized transactions or data manipulation. Future research is expected to further identify the specific factors within forensic accounting and internal control that contribute to the detection of financial statement manipulation.